Evaluasi Implementasi Peraturan Daerah Nomor 03 Tahun 2018 Tentang Pajak Parkir Di Kota Pekanbaru - Elsa Monika; Nur Laila Meilani (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Regional Original Revenue (PAD) is a source of regional revenue that comes from several regional revenues and one of them is obtained from local tax revenues, one type of which is parking tax. In order to regulate parking tax management, Pekanbaru City Regional Regulation Number 03 of 2018 concerning Parking Tax was issued, which is implemented by the Pekanbaru City BAPENDA. In the Pekanbaru City Regional Regulation Number 2 of 2011 concerning Parking Tax in article 1 point 8, it states that "Parking Tax is a Tax on the administration of parking lots outside the road body, whether those provided are related to the principal business, including the provision of motorized vehicle parking spaces". The purpose of this study is the first to find out the evaluation of the implementation of Regional Regulation No. 2 of 2011 concerning Parking Tax in Pekanbaru City. The second is to identify the inhibiting factors of Regional Regulation Number 2 of 2011 concerning Parking Tax in Pekanbaru City. The theory used is William N. Dunn's theory using 6 indicators, namely: Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy. This research uses a type of descriptive analysis qualitative research. Using interview data collection techniques, observation and documentation. `The results of this study found that the implementation of regional regulations handled by the Pekanbaru City Regional Revenue Agency was quite satisfactory or good enough, although there were still some deficiencies in it, such as in terms of communication with third parties, there was still a lack of understanding by taxpayers of the importance of taxes, non-tax resources. people, as well as socio-economic conditions that affect the implementation of these regulations. So that there is still a need for improvement in implementing this regional regulation. So that the process of implementing the Pekanbaru City Regional Regulation Number 03 of 2018 Regarding Tax can run optimally and optimally, various factors and needs must always be improved to achieve the goals of the regulation.